Pain Management During Newborn Screening: Using YouTube to Disseminate Effective Pain Management Strategies. Issue 2 (April 2017) - Harrison, Denise; Reszel, Jessica; Dagg, Bill; Aubertin, Cheryl; Bueno, Mariana; Dunn, Sandra; Fuller, Ann; Harrold, JoAnn; Larocque, Catherine; Nicholls, Stuart; Sampson, Margaret
Abstract : To assess the reach, acceptability, and effect of the BSweet2Babies video showing breast-feeding, skin-to-skin care, and sucrose during blood sampling on intention to recommend the video or advocate for use of the interventions. In July 2014, the video and an electronic survey were produced and posted. After 1 year, the online viewer survey responses and YouTube analytics were analyzed. One year after posting, the BSweet2Babies video had 10 879 views from 125 countries and 187 (1.7%) viewers completed the survey. Most respondents were aware of the analgesic effects of breast-feeding, skin-to-skin care, and sucrose. Nearly all respondents ( n = 158, 92%) found the BSweet2Babies video to be a helpful resource and 146 (84%) answered that they would recommend the video to others. After viewing the video, 183 (98%) respondents answered that they would advocate for 1 or more of the interventions. The BSweet2Babies video showing effective pain treatment during blood sampling had a large reach but a very small response rate for the survey. Therefore, analysis of acceptability and effect on intention to recommend the video and advocate for the interventions depicted are limited. Further research is warranted to explore how to best evaluate videos delivered through social media and to determine the effect of the video to promote knowledge translation into clinical practice.